Phyto Pharmacological Perspective of Yashtimadhu Glycyrrhiza Glabra LINN A Review - Shashikant M Prajapati, Dr (International Journal of Pharmaceutical & Biological Archive, 2014)
Phyto Pharmacological Perspective of Yashtimadhu Glycyrrhiza Glabra LINN A Review